The Influence of Tax Sanctions, Service Quality, Compliance Costs, and E-Filing Implementation on Taxpayer Compliance - Allawiyah, Fitriana; Henni Rahayu Handayani (Universitas Pamulang, 2025)
This study aims to analyze the factors influencing taxpayer compliance, including tax sanctions, service quality, tax compliance costs, and the implementation of e-Filling. The research method used is a quantitative approach with data collection techniques through questionnaires distributed to students at Universitas Pamulang. The data obtained were analyzed using statistical methods to determine the relationship between independent and dependent variables. The results of the study indicate that tax sanctions and the implementation of e-Filling have a significant influence on taxpayer compliance. Meanwhile, service quality and tax compliance costs show a lower impact. The discussion in this study highlights the importance of improving tax services, the effectiveness of digital systems, and other factors that can enhance tax compliance. With these findings, it is hoped that the government and tax authorities can design more effective policies to increase awareness and taxpayer compliance.